Histórias de vidas e formação de uma comunidade camponesa: o caso da comunidade São Miguel de Murutinga em Abaetetuba-PA - PANTOJA, Dilcilene Ribeiro (2019)
The present work is based on the rescue and reconstitution of the formation history of the community of São Miguel de Murutinga, rural area of the municipality of Abaetetuba Pará. The objective is to encourage students, children of peasants and the community in general, of the place know their own identity, recovering and valuing their roots, keeping in mind the historical memory of the community. We start methodologically from open interviews, with the question of community emergence, video footage, photos and also a historic walk. The first interviewee was the community coordinator, who indicated Ms. Maria José, who had an essential role in the founding of the community with her brother Manoel Sávio, and was also the first catechist of the same. Following the appointment of Father Hilário Taplett, one of the founders of the community. And so, in turn, they indicate two masters who were members of the rice cooperative, a farmer and a retired teacher, contemplating the snowball methodology (Bernard, 1995) where the interviewees appear randomly from the indication. The reports indicate that the São Miguel de Murutinga Community has experienced intense mobilization since its community formation, with the struggle for land, education, the conquest of the municipal school, as well as electricity, and the creation of the rice cooperative which was fundamental for the economic aspect of the community, which came to be considered a reference and recognized as the 'illustrious' community of Murutinga, which are considered great achievements and source of pride for the community. And in the present moment the struggles continue mainly in the economic and organizational aspect with the strengthening of Family Agriculture. So the results presented here are the fruits of oral history, the recognition of the community and its residents as something of immense importance, loaded with values and founded in the struggle.